IDENTIFYING CHILDREN WITH AUTISM SPECTRUM DISORDER (ASD) AMONG MAINSTREAM PRESCHOOL TEACHERS IN KLANG VALLEY (Proceedings of International Conference on Special Education, 2023)
Malaysia, along with many other countries, made a pledge to all children to ensure that all their rights including the rights to education will be protected and promoted when the United Nations Convention on the Rights of the Child (CRC) was adopted. In line with that, inclusive education was introduced in the Education Act 1996 and has been established ever since. According to the Malaysian Education Blueprint (2013-2025), the goal was to have children of 5 years registered in a preschool whether if it is public or private because the period from birth to five years is extremely crucial for any child as these are vital in laying the foundation for children to nurture their cognitive, language, physical, social, emotional, behavioral development. This study investigates the knowledge level of mainstream preschool teachers in identifying children with ASD. By focusing on teachers’ knowledge, the research aims to provide a better understanding of the promotion of inclusive education in Malaysia’s preschools. A mixed-method approach was used in this study. 30 respondents who worked in the field of early childhood education were recruited for this study. An online questionnaire was sent out for respondents to answer. Six respondents were recruited for the interview session that followed. Findings show that the knowledge level of the respondents ranges between moderate to high with the majority having a high knowledge level. The findings also resulted that one of the most important factors that affect the respondents’ knowledge in identifying children with ASD is through hands-on experiences and training related to ASD. This study implies that mainstream preschool teachers need to be exposed to ASD children so that they can have hands-on experiences, which will further strengthen their knowledge on ASD to ensure that they can identify children with ASD in the future.